2015
DOI: 10.1098/rspb.2014.2192
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for rod monochromacy in sloths and armadillos suggests early subterranean history for Xenarthra

Abstract: Rod monochromacy is a rare condition in vertebrates characterized by the absence of cone photoreceptor cells. The resulting phenotype is colourblindness and low acuity vision in dim-light and blindness in bright-light conditions. Early reports of xenarthrans (armadillos, sloths and anteaters) suggest that they are rod monochromats, but this has not been tested with genomic data. We searched the genomes of Dasypus novemcinctus (nine-banded armadillo), Choloepus hoffmanni (Hoffmann's two-toed sloth) and Mylodon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…Three species-Odobenus rosmarus (walrus), Callorhinus ursinus (northern fur seal), Notoryctes typhlops (marsupial mole)-have intact coding sequences for complete or partial SWS1, but external evidence suggests that SWS1 cones are absent in each [68][69][70]. Our combined dataset describes 270 species with functional SWS1 cones, 214 of which have measured or predicted spectral tuning (electronic supplementary material, table S1), and 133 with nonfunctional SWS1 cones, a common trait in species occupying scotopic niches (see [2,12,17,49,54,[69][70][71] for discussion). Our novel sequence data increase the taxonomic coverage of SWS1 spectral tuning to 39 additional mammalian families.…”
Section: Resultsmentioning
confidence: 99%
“…Three species-Odobenus rosmarus (walrus), Callorhinus ursinus (northern fur seal), Notoryctes typhlops (marsupial mole)-have intact coding sequences for complete or partial SWS1, but external evidence suggests that SWS1 cones are absent in each [68][69][70]. Our combined dataset describes 270 species with functional SWS1 cones, 214 of which have measured or predicted spectral tuning (electronic supplementary material, table S1), and 133 with nonfunctional SWS1 cones, a common trait in species occupying scotopic niches (see [2,12,17,49,54,[69][70][71] for discussion). Our novel sequence data increase the taxonomic coverage of SWS1 spectral tuning to 39 additional mammalian families.…”
Section: Resultsmentioning
confidence: 99%
“…The nine-banded armadillo has a complement of inactivated cone phototransduction genes identical to the golden mole, and Hoffmann’s two-toed sloth possesses PDE6C and PDE6H pseudogenes. Emerling and Springer18 further confirmed that additional armadillo and sloth species possess an inactivated PDE6C , suggesting that RM is widespread in these animals 18. Although many of these species live above ground, several lines of evidence suggest that armadillos and sloths share a common ancestor that was likely subterranean and had little use for cone photoreceptors 18…”
Section: Rod Monochromacymentioning
confidence: 97%
“…The first is by annotating the gene product as a ‘low-quality protein’, a designation provided if EGA had to correct for frameshift indels and/or premature stop codons in the assembly to create the gene model. For example, the GNAT2 gene model for the nine-banded armadillo (NCBI Reference Sequence: XM_012530646.1), which was confirmed by Emerling and Springer18 to be inactivated, has the following annotation note: ’The sequence of the model RefSeq protein was modified relative to its source genomic sequence to represent the inferred CDS: deleted 3 bases in 2 codons; substituted 1 base at 1 genomic stop codon'. Both frameshift indels and premature stop codons can be present in an assembly due to sequencing and/or assembly errors, so the number of false positives likely correlates negatively with genome quality.…”
Section: Amelogenesis Imperfectamentioning
confidence: 98%
See 1 more Smart Citation
“…Xenarthrans are hypothesized to have evolved as ancestrally fossorial mammals (Simpson, 1931). Several traits characterizing this major mammalian lineage are used as evidence for this hypothesis, including the limb morphology of modern and fossil xenarthrans, the lack of color vision in living xenarthrans, and the xenarthrous articulation (Emerling and Springer, 2015;Frechkop, 1949;Jenkins, 1970;Nyakatura and Fischer, 2011;Olson et al, 2016;Vizcaíno and Milne, 2002). Xenarthrous articulations, or xenarthrae, are ancillary intervertebral articulations found across the posterior thoracic and lumbar vertebrae, spanning the post-diaphragmatic region of xenarthrans (e.g.…”
Section: Introductionmentioning
confidence: 99%